Green and Digital: Managing the Twin Transition toward Sustainable Development - Francis Mark A. Quimba; Ramonette B. Serafica; Connie Bayudan-Dacuycuy; Abigail E. Andrada; Neil Irwin S. Moreno (Philippine Institute for Development Studies (PIDS), 2023)
The global shift toward sustainability and increased digitalization is evident. Nations are integrating renewable energy, carbon emission reduction, and advancements in green technologies into their development plans. Simultaneously, Industry 4.0 has revealed the diverse ways technology influences human life. Rather than separate factors, these dual forces are interconnected elements that countries must navigate for sustainable progress. As countries continue to pursue development strategies, taking a closer look on this twin phenomenon is important. This study assesses how investments, labor, science, technology, innovation, and artificial intelligence contribute to this dual transformation. Through desk reviews and synthesized data, this paper highlights relevant initiatives, technology-related risks, and recommendations for addressing existing gaps. The study acknowledges existing government initiatives aligned with green transition and digitalization. However, it identifies persistent issues, such as inadequate investment in clean climate technologies, shortage of skilled workers in green sectors, and uncertainties regarding the sustainability of AI. To overcome these challenges, the paper proposes directions to bridge gaps, remove barriers to participation, and enhance capabilities, aiming to fully harness the potential of this combined transition.
Keywords: 330; Green transition; digitalization; labor; artificial intelligence; green investments; science; technology and innovation